2014
DOI: 10.1128/aem.02447-14
|View full text |Cite
|
Sign up to set email alerts
|

The Facultative Symbiont Rickettsia Protects an Invasive Whitefly against Entomopathogenic Pseudomonas syringae Strains

Abstract: bFacultative endosymbionts can benefit insect hosts in a variety of ways, including context-dependent roles, such as providing defense against pathogens. The role of some symbionts in defense may be overlooked, however, when pathogen infection is transient, sporadic, or asymptomatic. The facultative endosymbiont Rickettsia increases the fitness of the sweet potato whitefly (Bemisia tabaci) in some populations through mechanisms that are not yet understood. In this study, we investigated the role of Rickettsia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 45 publications
(65 reference statements)
4
67
0
Order By: Relevance
“…Cuticle‐associated bacteria of the leaf‐cutting ant Acromyrmex subterraneus protect workers from infection by entomopathogenic fungi . Similar studies have also been reported for other taxa, such as aphid, whitefly and beewolf. Synergistic effects between entomopathogens and insect microbial associates have also been reported.…”
Section: Discussionsupporting
confidence: 74%
“…Cuticle‐associated bacteria of the leaf‐cutting ant Acromyrmex subterraneus protect workers from infection by entomopathogenic fungi . Similar studies have also been reported for other taxa, such as aphid, whitefly and beewolf. Synergistic effects between entomopathogens and insect microbial associates have also been reported.…”
Section: Discussionsupporting
confidence: 74%
“…In all isolates the colony forming units were uncountable at zero dilution. This result in conformity with Adams et al, (2014), Kwiatkowski et al, (2015), Mensah and Twumasi (2016), Hendry et al, (2014), even they could find 40 plates out of 1440 were having uncountable colonies due to spreading of the colonies. It was observed that the plates were having uncountable colonies at zero dilution because of more number of colonies and due to spreading.…”
Section: Isolation and Characterization Of Six Bacterial Isolatessupporting
confidence: 91%
“…Members are known to induce a variety of reproductive manipulations, including male killing in ladybird beetles (Adalia bipunctata) (Werren et al, 1994;Hurst et al, 1999;Majerus et al, 1999) and parthenogenesis induction in parasitoid wasps (Pnigalio soemius; Neochrysocharis formosa) (Hagimori et al, 2006;Giorgini et al, 2010). Rickettsia symbiont infection can also be protective, enhancing resistance of aphids (Acyrthosiphon pisum) to fungal attack and whiteflies (Bemisia tabaci) to bacterial challenge (Łukasik et al, 2013;Hendry et al, 2014). Of significance to the study of vectors, Rickettsia are also known to increase the competence of Bemisia whiteflies for the transmission of tomato leaf curl virus (Kliot et al, 2014).…”
Section: Introductionmentioning
confidence: 99%